2022
DOI: 10.3390/ijerph20010075
|View full text |Cite
|
Sign up to set email alerts
|

Population Attributable Fraction of Gas Stoves and Childhood Asthma in the United States

Abstract: Indoor gas stove use for cooking is associated with an increased risk of current asthma among children and is prevalent in 35% of households in the United States (US). The population-level implications of gas cooking are largely unrecognized. We quantified the population attributable fraction (PAF) for gas stove use and current childhood asthma in the US. Effect sizes previously reported by meta-analyses for current asthma (Odds Ratio = 1.34, 95% Confidence Interval (CI) = 1.12–1.57) were utilized in the PAF e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 6 publications
1
40
1
Order By: Relevance
“…53 Using this meta-analytic estimate, one study calculated that about 13% of all pediatric asthma cases in the US were attributable to gas cooking. 54 Elsewhere, a simulation study estimated that replacing gas stoves would reduce severe asthma attacks by 7% in an urban population. 55 Our effect estimates are larger than what we might expect given anticipated air pollution exposure reductions from gas to induction cooking transitions and existing estimates of the health effects from NO 2 exposures (Methods).…”
Section: Discussionmentioning
confidence: 99%
“…53 Using this meta-analytic estimate, one study calculated that about 13% of all pediatric asthma cases in the US were attributable to gas cooking. 54 Elsewhere, a simulation study estimated that replacing gas stoves would reduce severe asthma attacks by 7% in an urban population. 55 Our effect estimates are larger than what we might expect given anticipated air pollution exposure reductions from gas to induction cooking transitions and existing estimates of the health effects from NO 2 exposures (Methods).…”
Section: Discussionmentioning
confidence: 99%
“…A 2013 systematic review and meta-analysis of gas cooking and current asthma ( n = 10 studies in North America and Europe) reported a pooled odds ratio of 1.34 with a 95% confidence interval of 1.12–1.57 ( 6 ). A recent publication used this effect to estimate that 13% of childhood asthma could be prevented by eliminating gas cooking ( 7 ), but that does not mean that eliminating gas cooking is the only way to prevent those asthma cases. That article helped spur the CPSC and media to focus on the potential health hazards.…”
Section: What Are the Adverse Health Effects Of Gas Stoves?mentioning
confidence: 99%
“…First, constraining estimates of indoor NO 2 exposure from direct measurements of indoor concentrations is challenging because the data are sparse and because observed concentrations can fluctuate with ventilation and stove use (21,22). Second, studies that correlate health outcomes with the presence or absence of a gas stove (rather than with direct pollutant exposure) typically do not capture large differences in housing size and layout, ventilation, or behavior that may substantively affect exposure across groups (23)(24)(25), hindering investigations of health disparities mediated through such factors. Existing meta-analyses calculating odds ratios (ORs) of specific health outcomes associated with gas stoves have relied either on correlations between measured indoor NO 2 concentrations and health outcomes, as opposed to directly quantifying NO 2 exposure, or have used the presence of gas stoves as a proxy for NO 2 exposure (16,26).…”
Section: Introductionmentioning
confidence: 99%